KEBERADAAN KELUARGA TKW JAWA TIMUR BERBASIS ARENA PRODUKSI KULTURAL (Forum Ilmu Sosial, 2014)
This study examines the issues facing families in East Java Indonesia TKW based habitus and the spaces where they lived and the role of space in the arena or producing culture family TKW in East Java. Through this study, qualitative approach to generate findings that consumption pattern of families and family life style TKW tend to consumtion. While that view of life off his wife into a TKW is not based on the value of culture and religion. Parenting family TKW which is not presents, are likely to have an impact on children's delinquency. While the husband who left a lot of do behavior deviant. As long as there is no institution that conducts training specifically on the family TKW.